Leadership development of health and social care professionals: a systematic review. Issue 4 (25th June 2020) - McGowan, Emer; Hale, Jennifer; Bezner, Janet; Harwood, Kenneth; Green-Wilson, Jennifer; Stokes, Emma
Abstract : The need to develop leaders across all levels of the health system including clinical staff has been recognised. Investments are made by healthcare organisations each year to develop leadership within their workforce hence there is a need to evaluate these development programmes to investigate whether the stated objectives have been achieved. The aim of this review was to systematically review published literature on the effect of leadership development for health and social care professionals (HSCPs). The databases, CINAHL, EMBASE, ERIC, Medline, PsychInfo, Scopus and Web of Science, were systematically searched. After screening and quality analysis, nine full-text articles were included in the review. The included studies demonstrated a range of methodological quality and there was high variability in the leadership development programmes in terms of programme length, content, structure, participants and evaluation methods. Transformational leadership was the leadership model most frequently employed. The reported results suggest that these educational interventions have positive effects on participants such as improved leadership behaviours, increased confidence and workplace engagement. However, the mixed methodological quality of the studies and high variability between the courses mean that definitive recommendations for leadership development programmes for HSCPs cannot be made. High-quality, longitudinal studies using rigorous evaluation methods are needed to provide the necessary evidence to inform the development of future programmes.